La memoria fotografica dell'architettura Restituzioni prospettiche e ricostruzioni - Agnello, Fabrizio (Forme del disegno, 2023)
Perspective restitution is the inverse process of perspective and is therefore rooted in descriptive geometry; when this technique is applied to the restitution of dimensions from photos, it enters the territories of photogrammetry. The position on the border between two disciplines, different but related, has caused the solitude of perspective restitution from photos: rarely mentioned in studies on descriptive geometry, it is completely ignored in those dedicated to photogrammetry. Yet, perspective restitution is the only tool that allows us to reconstruct, from a single image, the 3D layout of a building. In his 1930 book dedicated to 'Metrophotography', Henri Deneux had highlighted, probably for the first time, the possibility of reconstructing, from a single photo, buildings or parts of them damaged by war events (Deneux referred to monuments damaged by the bombings of World War I). Today, digital drawing and modelling tools enable us to overcome many of the difficulties that affected perspective restitution from photos with traditional drawing tools. This volume illustrates the theoretical assumptions and the drawing and modelling techniques that allow us to achieve the 3D reconstruction of buildings and urban scenarios that no longer exist from one or few images.